A FORMA DA CARAPAÇA EM AEGLA (CRUSTACEA: ANOMURA) - Oliveira, Aline Rossi de (2013)
Crabs used in this study belong to the family Aeglidae occur in inland waters and are endemic to southern South America. They have oval body and flattened dorsoventrally and carapace marked by a complex arrangement of sutures. Aeglidae has only one current genus, Aegla Leach, 1820 consisting of approximately 70 described species, divided by more complete phylogeny in 5 subclados: A-B, consisting of species of southern Argentina and Chile; C, along the Paraná Basin; D over the affluent west and the Basin of Uruguay and E, along the Uruguay River Basin. In the present study we applied geometric morphometric techniques in Brazilian eglídeos for better understanding of morphological variation inter and intra-specific, is investigating the possible patterns of variation in the shape of the carapace is associated with local adaptations of populations or whether they represent evolutionary patterns set within the different lineages. We used three species with a high degree of relatedness of subclade C, Aegla castro, A. parana and A. schmitti and even a species collected for previous studies on the river Bananas in Guarapuava - PR, and three closely related species also, but in another subclade (subclade E), A. ligulata, A. longirostri and A. inconspicua. Reported a significant difference in the shape of the carapace among species and among populations of the same species and even distinct clades and in the context of this study, some allied with the carapace shape more similar to each other than with their species clade. We can say, therefore, that these crabs have a fixed shape of the carapace, which allowed us to recognize them using geometric morphometrics and part plastic, causing populations to differ according to the characteristics of the environment in which they live.